Tenthaus Oslo - en inkluderende organisatorisk modell for framtidas kulturskoleelev - Gry O. Ulrichsen (Cappelen Damm Akademisk NOASP, 2017)
The aim of this article is to contribute more knowledge about how arts educational practice in the school context can be understood and developed. The cooperation between Tentahaus Oslo (TO), an initiative driven by artists, and the basic education section for minority students at an upper secondary school is brought forward as an alternative to more traditional forms of encounters with art and art communication in basic education and in the voluntary music and performing arts school. The article points out how the didactic thinking meets structural challenges and opens up spaces where participatory artistic processes and pedagogical processes are integrated. Didactic components like time, space and exchange, an extended time perspective, the placement of an atelier in school, a public exhibition space attached to the atelier, as well as exchange between teachers and the artist, appear as constitutive elements in the systematic cooperation between the fields. In a cross curricular perpsective on learning the article suggests that experiences from the cooperation might have transfer value to a more general school context and to the organization of the music and performing arts school and its teaching practice. The article also directs the attention to didactic arrangements that might increase the amount of students with a heterogenous cultural background in the music and performing arts school. In a larger perspective the importance of encounters with art in an educational context might enhance democratic thinking. The methodological approach is aletic hermeneutics, where empirical material is generated through narrative and critical dialogue.